2022
DOI: 10.1002/ccr3.5653
|View full text |Cite
|
Sign up to set email alerts
|

Gastric trichobezoar: An uncommon cause of epigastric pain: A case report

Abstract: Trichobezoars are foreign and indigestible materials in the gastrointestinal tract and are usually found in psychiatric females, who often deny eating their own hair, but also at situations of gastric dysmotility and prior gastric surgery. Although rare, gastric trichobezoar should not be forgotten as a differential diagnosis in females presenting with vague epigastric pain. Its treatment well in time will prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Trichobezoars rarely occur in everyday clinical work. They were discovered in 1779 during an autopsy of a patient who died of gastric perforation [10]. Nowadays, they are described in the surgical literature, and fewer cases are found in psychiatric sources [14].…”
Section: Discussionmentioning
confidence: 99%
“…Trichobezoars rarely occur in everyday clinical work. They were discovered in 1779 during an autopsy of a patient who died of gastric perforation [10]. Nowadays, they are described in the surgical literature, and fewer cases are found in psychiatric sources [14].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Although TTM and TPH are frequently encountered in trichobezoar patients with clinical symptoms,[ 8 ] the incidence of gastric trichobezoars is around 0.5% in TTM and TPH patient groups. [ 9 ] Although the ingestion of indigestible foreign objects such as hair, nails, and plastic is relatively common in society, low-frequency states of the disease do not constitute a clinical manifestation, and continued ingestion behavior in some patients may present with fatal complications. [ 9 ] There is no information on how much time and how much hair it takes for TPH to transform into a symptomatic trichobezoar.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Although the ingestion of indigestible foreign objects such as hair, nails, and plastic is relatively common in society, low-frequency states of the disease do not constitute a clinical manifestation, and continued ingestion behavior in some patients may present with fatal complications. [ 9 ] There is no information on how much time and how much hair it takes for TPH to transform into a symptomatic trichobezoar. In our series, rapunzel syndrome was encountered in one of our patients who was the same age and had hair ingestion habit for 3 years, while gastric bezoar and satellite ileal bezoar were encountered in the other.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no precise statistical data on the incidence of gastric trichobezoar in this risk group. In general, it is estimated that the incidence of trichobezoar is around 0.5 % [3] , [4] . The manifestations caused will be related to the location and extension of the trichobezoar, so they are unspecific, giving great relevance to the psychiatric history as a plausible risk factor [2] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…However, another point to highlight is the fact that in the absence of psychiatric history and lack of information, the surgical diagnosis can identify psychological or psychiatric factors not previously investigated, which can definitively solve the primary cause, preventing the recurrence of trichobezoar in the future. Case reports and case series have reported that trichophagia is a behavior that is strongly associated with trichotillomania [2] , [3] , [4] , [5] . However, involuntary nocturnal trichotillomania is more complex to diagnose and treat, and may be referred almost exclusively by an observant family member.…”
Section: Introductionmentioning
confidence: 99%